Body Dismorphic Disorder Tendency to Stress Level in Female Adolescences - Fazriyani, Ghina Yustina; Rahayu, Desi Ariyana (Media Keperawatan Indonesia, 2019)
Body Dismorphic Disorder(BDD) tendency is a series of symptoms experienced by a person that leads to dissatisfaction with the physical appearance or body appearance that usually occurs in adolescent girls. Where female adolescences have more obsession with physical appearance and the desire to have a perfect body shape, so they make various efforts to overcome the shortcomings in terms of physical. This will result in the burden of mind on young women when their desires cannot be achieved, and have an impact on the emergence of stress.The purpose of this research is to determine the relationship between the tendency of BDD to stress levels in female adolescences in a high school. The type of this research is quantitative descriptive correlational research approach with crosssectional design. The sample of this study was 216 female adolescent respondents with a simple random sampling technique. Data analysis by using test Rank Spearman correlation test. Research result shows that of tendency BDD in female adolescences in the ccategory of high BDD tendencies (55,6%) and low BDD tendency category (44,4%). The stress level in female adolescences in the mild stress category (33,3%), normal category (30,1%), moderate stress category (30,6%), and severe stress category (6%). Conclusion showed the relationship between the tendency of BDD to stress levels (p = 0,000) with a correlation coefficient of 0.646, i.e. the higher of BDDÂ  tendency, the more it will influence the stress level.